2018
DOI: 10.6000/2292-2598.2018.06.02.3
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards Sexuality in Males and Females with Intellectual Disabilities: Indonesia Setting

Abstract: Abstract:Introduction: sexual and reproductive rights in individuals with intellectual disabilities (ID), particularly in developing countries, are often neglected. Although affected individuals never complained, the problems were found augmented from the affected families. Over the last two decades, parents and professionals acknowledged sexual and reproductive right and try to accommodate these needs. Indonesia, a developing country with a strong religious and culture beliefs may has different perspectives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Another study reported this difference between the youngest (20-to 29-year-olds) and the 50 to 59-year-old group for sexual rights for women [27]. Other studies involving staff [26,29,30,50], students with support work experience [34], community [44], and mixed samples [47,53] did not find that relationship.…”
Section: Factors Related To More Negative or Positive Attitudesmentioning
confidence: 98%
See 4 more Smart Citations
“…Another study reported this difference between the youngest (20-to 29-year-olds) and the 50 to 59-year-old group for sexual rights for women [27]. Other studies involving staff [26,29,30,50], students with support work experience [34], community [44], and mixed samples [47,53] did not find that relationship.…”
Section: Factors Related To More Negative or Positive Attitudesmentioning
confidence: 98%
“…On the contrary, a study with staff and community samples found more negative attitudes in women populations, specifically in regard to sexual intercourse, parenting, marriage and petting; and men attitudes were more negative towards men kissing with a same-gender partner [51]. Finally, other studies did not find clear relationships between gender and attitudes in staff [26,27], community [39,44] or familystaff-community samples [46,47,53].…”
Section: Factors Related To More Negative or Positive Attitudesmentioning
confidence: 98%
See 3 more Smart Citations